2002
DOI: 10.1111/j.0004-8666.2002.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and predictive values of risk factors for neonatal group B streptococcal sepsis

Abstract: Neither early antenatal screening nor clinical risk factors are reliable predictors of intra-partum GBS carriage. Intra-partum antibiotic prophylaxis based on GBS carriage or risk factors when carrier status is unknown would involve approximately 35% of women, compared with approximately 16% if based on risk factors only Both strategies would prevent similar proportions of neonatal deaths from GBS sepsis. Compliance with a preventive protocol is the most likely determinant of its overall effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…13,20 The dominant pathogen in sepsis among term neonates is GBS, accounting for 59% of term cases in one report. 21 The rate of women with rupture of membranes 18 hours or longer in our population (10.9%) was comparable with the rates reported by others, ranging from 7.8% to 12.0%, 6,9,13,22 although these populations included preterm births, which were excluded in our analysis.…”
Section: Discussionsupporting
confidence: 89%
“…13,20 The dominant pathogen in sepsis among term neonates is GBS, accounting for 59% of term cases in one report. 21 The rate of women with rupture of membranes 18 hours or longer in our population (10.9%) was comparable with the rates reported by others, ranging from 7.8% to 12.0%, 6,9,13,22 although these populations included preterm births, which were excluded in our analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Vaginal colonisation occurs in 11–30% of all pregnant women [4-6] and 50–75% of their infants become colonised usually during labour or birth. There is clear evidence that intrapartum colonisation is strongly associated with EOGBS sepsis [7] which has a case-fatality of approximately 4%[1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a survey of Australian obstetricians and neonatologists found that 44% preferred a risk‐based approach 30 . Advocates for risk‐based policies indicate concerns over rare but potentially serious anaphylactic reactions to antibiotics, the risk of developing antibiotic resistance, results of health economic analyses, difficulties with obtaining timely recto‐vaginal samples and laboratories employing suboptimal culture techniques 11,31,32 . It is estimated within Australia that 30–35% of all women in labour would receive IAP under a universal screening strategy, whereas a risk‐based approach would mean only 15–20% being exposed to antibiotics 20,31 …”
mentioning
confidence: 99%